Peningkatan Konsentrasi Belajar Pembelajaran Tematik Menggunakan Model Problem Based Learning Kelas II - Nursolehatun, Tika (Paedagogie, 2023)
This research is a classroom action research conducted in two cycles, starting from (1) planning, (2) implementation, (3) observation, and (4) reflection. The purpose of this study was to increase the learning concentration of class II students at Kanisius Totogan Elementary School in thematic learning using the problem-based learning model. The subjects of this study were 20 students of grade II SD Kanisius Totogan consisting of 11 boys and 9 girls. Data collection techniques were carried out by observation and interviews. Data were analyzed quantitatively and qualitatively. The results showed that students' learning concentration increased in thematic learning through the application of problem-based learning models. Students' learning concentration experienced an increase in the low pre-cycle (39.5%), the first cycle (49.5%) was moderate, and the second cycle (82.75%) was very high. Keywords: learning concentration, thematic, problem based learning